FAKTOR YANG MEMPENGARUHI PENYESUAIAN DIRI REMAJA PUTUS SEKOLAH DI JORONG BATANG KARIANG KECAMATAN KAMANG BARU KABUPATEN SIJUNJUNG - Arpa, Desi; Kasih, Fitria; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
Based on problem studied that researcher found look at phenomenon is the field any adolescent droupout and some of his friend did not want out of the house to hang out and there is also a loner because do not like crowds. Based on the phenomenon that the researcher raisaid concerns about: what were factors affect adolescent adjustment droup out in Batang Kariang Kecamatan Kamang Baru Kabupaten Sijunjung. The purposes these studied were to discribe: 1). Factor that affect adolescent adjustment droup out views of the personality 2). Factor that affect adolescent adjustment droup out views of theÂ  environment. This researchd was quantitative descriptive research that seeks to describe the situation for what it is. The study population amounted to 51 peoples. The techniques used in this sampling were a sampling technique and a total sample size of 51 people. The instrument used in this study is questionnaire. As for the use of data analysis is techniques percentage. The research results revealed that: 1). Factors that affect adolescent adjustment drop out seen in the category of personality pretty much, it can be seen from the results of the study showed the number 82.35 % 2 ). Factors that affect adolescent adjustment dropout seen enough of the environment, it can be seen from the results of the study showed the number 88.23 %.